1977
DOI: 10.3758/bf03197389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of distorted auditory and of rhyming cues on retrieval of tip-of-the-tongue words by poets and nonpoets

Abstract: the boundaries of that word are encountered. Then, when that word is read, it appears extremely and excitingly fitting, and some of the emotional accompaniments to solving a TOT may be engaged. Reading clearly involves a constructive process, highly influenced by systematic context effects (Hochberg, 1970;Rayner, 1975;Tulving & Gold, 1963). Brown (1970), in a largely ignored discussion of the causes of the TOT phenomenon, notes that reading makes use of a noticing order, that is, a regular order of processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
(12 reference statements)
2
16
2
1
Order By: Relevance
“…For this reason, a recognition test can assess whether the TOT items are actually of higher activation than items not in a TOT. Some TOT studies have looked at recognition of targets after the rememberers experienced TOTs and when they did not (e.g., Burke et aI., 1991;Kozlowski, 1977;Schwartz, 1998;Schwartz & Smith, 1997;Schwartz et aI., in press;Smith, Balfour, & 1. M. Brown, 1994;Widner, Smith, & Graziano, 1996).…”
Section: Support For the Direct-access Viewmentioning
confidence: 99%
“…For this reason, a recognition test can assess whether the TOT items are actually of higher activation than items not in a TOT. Some TOT studies have looked at recognition of targets after the rememberers experienced TOTs and when they did not (e.g., Burke et aI., 1991;Kozlowski, 1977;Schwartz, 1998;Schwartz & Smith, 1997;Schwartz et aI., in press;Smith, Balfour, & 1. M. Brown, 1994;Widner, Smith, & Graziano, 1996).…”
Section: Support For the Direct-access Viewmentioning
confidence: 99%
“…For instance, Koriat and Lieblich (1974 discovered that TOTs occurred on I 1% of retrievals, whereas Yaniv and Meyer (1987) noted TOT rates ofl 8% and 15% in two separate experiments. Kozlowski (1977) found TOTs on 15% and 13% of retrievals in two studies. In a study testing only older adults, Finley and Sharp (1989) used trivia questions to elicit target words and discovered a relatively high rate of 26% TOTs.…”
Section: Incidence Over Itemsmentioning
confidence: 99%
“…In a creative exploration into the role of related words in the TOT experience, Kozlowski (1977) used a poetic analogy. He assumed that the rhythm, rhyme, structure, and meaning of standard poetic verse leads the reader toward a target word in the same manner that an individual uses fragmentary meaning and structural information during a TOT to help locate the missing target word.…”
Section: Similar Wordsmentioning
confidence: 99%
“…However, TOT research has almost exclusively used dichotomous judgments, either yes for a TOT or no for an n-TOT (the state of not being in a TOT). An exception is a study by Kozlowski (1977), who found that "extreme" TOTs were followed by higher recognition of unrecalled targets than were "moderate" TOTs or n-TOTs (see, also, Gardiner, Craik, & Bleasdale, 1973). Thus, it seems likely that rememberers can and do distinguish intensities of TOTs, similar to the distinctions they can make between stronger and weaker feelings of knowing.…”
mentioning
confidence: 97%